IMPLEMENTATION OF GAMIFICATION IN CAPITAL MARKETS COURSE PERBANAS INSTITUTE - Januponsa Dio Firizqi; Fangky Antoneus Sorongan; Dwi Atmodjo Wismono Prapto; Richardus Eko Indrajit (Informatika, Universitas Jenderal Soedirman, 2022)
Along with technological developments and the occurrence of a pandemic caused by the Covid-19 Virus, many activities are carried out digitally and remotely. This pandemic causes disruption and constraints in various industries, sections or sectors. Higher education is one of the sectors experiencing disruption during the Covid-19 pandemic, where teaching and learning processes that were previously held face-to-face in the classroom have turned into virtual spaces. This makes lecturers and students have to be ready to adapt and carry out the teaching and learning process by utilizing technology such as Learning Management Systems, Video Conferences, and Campus Academic Systems. Not infrequently the teaching and learning process becomes monotonous, boring and limited in conveying and receiving the material provided. With the development of information technology can produce a concept of teaching and learning with the help of technology which is commonly called Gamification. The concept of Gamification using Mechanics Dynamic Emotional (MDE) Framework adopts elements of the game concept into the teaching and learning process because it has Mechanical, Dynamics, and Emotional aspects so that learning conditions can be created that are more interesting, fun and enjoyable. The MDE framework will be integrated into e-learning using the Research and Development (R&D) method. The R & D method is a method that is able to improve a product or make a product better. The stages in this study were made into 6 steps, namely: problem identification, data collection, analysis, village, trial and implementation, evaluation. And it can be said that by implementing gamification in lectures in the capital market at e-learning Perbanas succeeded in increasing interest, interaction, and learning atmosphere.